2018
DOI: 10.15761/docr.1000261
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different oral care systems: Results for Germany and selected highly developed countries. An update of a former study

Abstract: Objective: Evaluation of different types of oral care systems by means of new analytical tools that facilitate the obtention of quantifiable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…In countries where oral health is integrated in the national health systems, hypothetically this may contribute to a greater value attributed to oral health, whereas in countries where oral health is based on insurance-based systems, the apprehend value may differ. Preventive and tooth-preserving strategies are the gold standard public measures [ 2 ], yet patients’ adherence to these strategies strongly depend on how they value such care [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In countries where oral health is integrated in the national health systems, hypothetically this may contribute to a greater value attributed to oral health, whereas in countries where oral health is based on insurance-based systems, the apprehend value may differ. Preventive and tooth-preserving strategies are the gold standard public measures [ 2 ], yet patients’ adherence to these strategies strongly depend on how they value such care [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is highly relevant to patients. Tooth loss is thus an epidemiological key variable and is also used to assess the quality of a dental healthcare [5]. Tooth loss exceeding a certain number of teeth has a significant impact on chewing function, nutrition, speech, and esthetics.…”
Section: Introductionmentioning
confidence: 99%
“…dental care), high out-of-pocket expenses, and other cost participation plans, which eventually constitute major financial barriers in healthcare access and use by socioeconomically deprived groups, characterized by a low education, a low occupation, and a low income ( Bazin et al, 2006 , Petrelli et al, 2019 , Guessous, 2011 , Feral-Pierssens et al, 2020 , van Doorslaer et al, 2000 , Guessous et al, 2014 ). In particular, we observed that dental care was the most common type of care forgone, which is explained by the fact that dental care is not included in the mandatory health insurance plan in Switzerland, and may constitute a major financial burden for economically disadvantaged individuals ( Guessous et al, 2014 , Sandoval et al, 2021 , Saekel, 2016 ). Furthermore, previous research has also highlighted the role of psychosocial factors, such as personal beliefs, fear of stigma, or mistrust in the medical system, which are often driven by socioeconomic and cultural determinants (i.e.…”
Section: Discussionmentioning
confidence: 99%